Ion dynamics in quasi-perpendicular collisionless interplanetary shocks: a case study - Gedalin, Michael; Droege, Wolfgang (Frontiers in Physics, 2013)
Interplanetary shocks are believed to play an important role in the acceleration of charged particles in the heliosphere. While the acceleration to high energies proceeds via the diffusive mechanism at the scales exceeding by far the shock width, the initial stage (injection) should occur at the shock itself. Numerical tracing of ions is done in a model quasi-perpendicular shock front with a typical interplanetary shock parameters (Mach number, upstream ion temperature). The analysis of the distribution of the transmitted solar wind is used to adjust the cross-shock potential which is not directly measured. It is found that, for typical upstream ion temperatures, acceleration of the ions from the tail of the solar wind distribution is unlikely. Pickup ions with a shell distribution are found to be effectively energized and may be injected into further diffusive acceleration regime. Pre-accelerated ions are efficiently upscaled in energies. A part of these ions is returned to the upstream region where they can further be diffusively accelerated.